Six Sigma: Just More of the Same?. Issue 2 (21st February 2013) - Roth, William F.
Abstract This article tells how Six Sigma builds on a progression of earlier approaches to increasing workplace efficiencies and improving product quality. The article explores the productivity improving contributions of Adam Smith, Frederick Taylor, W. Edwards Deming, the Systems school, and Michael Hammer, showing that Six Sigma ends up combining the strengths of these contributions. It offers an alternative approach focused more on the non‐quantifiable elements, an approach that might be the next step in the progression.